Partial nephrectomy for a Bosniak IV cystic renal mass mimicking a simple renal cyst adjacent to a solid renal tumor - Oka, Toshiki (IJU Case Rep, 2020)
INTRODUCTION: Renal tumors are often associated with renal cysts. Meanwhile, in some cases there are challenging issues of how to diagnose renal cystic tumors and to decide surgical procedures. CASE PRESENTATION: A 75‐year‐old man was referred to our department for a 21‐mm tumor by his left kidney. Contrast‐enhanced computed tomography showed an intense contrast uptake the tumor, which was adjacent to a 64‐mm unilocular renal cyst with no contrasting effects. It was clinically diagnosed as renal cell carcinoma, stage T1aN0M0, and treated with robot‐assisted partial nephrectomy, for both the solid tumor and the adjacent cyst. Pathological findings revealed a tumor cell clump within the cyst wall, concurrent with the renal cell carcinoma. The patient has remained free of disease at 1 year after surgery. CONCLUSION: A partial nephrectomy that includes the entire cyst wall should be considered for renal tumor associated with unilocular renal cyst.